Cover Image, Volume 42, Issue 8. (16th July 2018) - He, Fengqi; Li, Xinxi; Zhang, Guoqing; Zhong, Guanjin; He, Jieshan
Abstract : The cover image, by Fengqi He et al., is based on the Research Paper Experimental investigation of thermal management system for lithium ion batteries module with coupling effect by heat sheets and phase change materials, https://doi.org/10.1002/er.4081 .